Integrating Watershed and Small Scale Effects of Rain Water Collecting in India (International Journal of Innovative Research in Computer Science & Technology, 2021)
In India, agricultural productivity has  become more reliant on groundwater, resulting in  groundwater depletion. Rainfall collecting (RWH) for  watershed replenishment is being considered as one  solution to the groundwater problem. This may be seen in  the increased number of watershed development projects  in which RWH is a key architectural component.  Understanding the overall impact of these developmental  measures is critical for ensuring a beneficial net effect on  groundwater both regionally and across a catchment. As a  result, the emphasis of this research is on the hydrological  impacts of RWH for recharge in rural areas at the micro  (individual structure) and regional levels. Surprisingly  limited experimental proof of the stated positive impacts  at the local level exists, and there are several possible  negative consequences at the watershed scale. Field  research on the watersheds level is underrepresented, and  it is mainly handled via models. Modeling is seen to be an  useful method for expanding limited field information,  and scenarios analyses might be utilized to assess  possible consequences. Many prior RWH modeling  studies, on the other hand, either had a narrow focus or  were based on insufficient data. In addition to enhancing  field data collection, new modeling approaches must be  developed. As possible new options, greater use of distant  sensors and advanced statistical tools are discussed. In  addition, some evaluation criteria are provided for  evaluating the hydrological and other consequences of  RWH on a local and regional scale as part of drainage  improvement.
Keywords: Aquifer Recharges; Groundwater Managed; Water Balance; Water Storage; Watershed Development